QUANTITATIVE ANALYSIS OF MACROPHAGES IN WOUND HEALING OF RAT SKIN SUBJECTED TO LOUD NOISE STRESS - Rafi, Aisha; Khan, Muhammad Yunus; Minhas, Liaqat Ali (Journal of Ayub Medical College Abbottabad, 2014)
Background: Factors affecting skin wound healing have always been a central consideration in medical practice. Loud noise is biological stressor affecting the body systems at various levels. The present study was taken to study the effect of loud noise stress on the macrophages during wound healing process in male rat skin. Method: One hundred and eighty male Sprague Dawley rats were randomly divided into control group-A and experimental group-B. Each group comprised 90 animals. Control and experimental groups were further subdivided into three subgroups of 30 animals each, corresponding to the day of sacrifice of animals, i.e., day 3, 5 and 7 after surgery. After induction of local anaesthesia a linear full thickness incision paravertebral to thoracic spine was made on the dorsum of rat. The experimental group B was exposed to loud noise stimulus (recorded noise of aero planes and gun fire) set at 97dBA to 102 dBA with a sound level meter. The animals were decapitated on day 3, 5 and 7 after surgery. Tissue was processed for paraffin embedding and stained by Hematoxylin and Eosin and Mallory's trichrome stain. Data was collected for the incisional space of the wound. Quantitative data of number of macrophages was analysed by Student's' test for the detection of any significant differences between the mean number in the experimental and control groups. All the quantitative data was expressed as means±SE. A p-value of ‰¤0.05 was considered statistically significant. Results: In this study macrophages were decreased statistically significantly at day 3 after surgery and thereafter increased significantly on day 5 and 7 after surgery in the experimental subgroups as compared to their match control subgroups. Conclusion: These results show that loud noise stress affects the cells (macrophages) involved in the healing of the wound therefore it is expected to have impact on the stages of wound healing. Keywords: Macrophages, wound, healing, stress, noise